Assembly of reduced graphene oxides into a three-dimensional porous structure via confinement within robust cellulose oligomer networks. Issue 66 (27th November 2019) - Hata, Yuuki; Saito, Yoshitaka; Sawada, Toshiki; Matsumoto, Hidetoshi; Serizawa, Takeshi
Abstract : Reduced graphene oxides were assembled into a fine porous structure via confinement within robust cellulose oligomer networks. Abstract : The assembly of nanomaterials into a networked superstructure is a strategy used to construct macroscopic porous materials having the functional properties of nanomaterials. However, because nanomaterials generally prefer densely packed assembled states owing to their high surface energies, the construction of a fine porous structure is still a challenge. In this study, we demonstrate the assembly of reduced graphene oxides (rGOs) into a fine porous structure via confinement within robust cellulose oligomer networks. The confinement of rGOs within cellulose oligomer networks was achieved in one step via the enzymatic synthesis of cellulose oligomers. When the resultant cellulose oligomer gels confining rGOs were reduced by hydrogen iodide, the robust cellulose oligomer networks served as a confinement space for rGOs, preventing excessive aggregation of the rGOs and thus encouraging their assembly into a fine porous structure. Electrochemical measurements revealed that the porous rGO materials could act as electrode materials for supercapacitors. Our strategy based on simple physical confinement will allow for the creation of functional porous materials with excellent nanomorphologies from various nanomaterials.